RARE EARTH ELEMENTS GEOCHEMISTRY OF LAOWAN GOLD DEPOSIT IN HENAN PROVINCE: TRACE TO SOURCE OF ORE-FORMING MATERIALS - Xie Q.; Xu X.; Li X.; Chen T.; Lu S. (My University, 2006)
The compositions of REE in quartz and pyrite from the main stage of the Laowan gold deposit in Henan Province and that in quartz from Laowan granite were determined by inductively coupled plasma-mass-spectrometry (ICP-MS) to trace the source of ore-forming materials. Meanwhile, the REE compositions of the deposit ore, granite and metamorphic wall rock were also considered for comparative studies in detail. The range of ∑REE of quartz and pyrite from the deposit ores is 4.18×10-6-30.91×10-6, the average of ∑REE is 13.39×10-6, and the average of ∑REE of quartz in the Laowan granite is 6.68×10-6. There is no distinct difference of REE parameters between the deposit ore quartz and granite quartz. The quartz in gold deposit has the same REE particular parameters as quartzes from Laowan granite, such as δEu, δCe (La/Yb)N and (La/Sm)N, partition degree of LREE to HREE, especially, the chondrite-normalized REE patterns, but no similarity to those from metamorphic wall rock, which shows that ore-forming hydrothermal fluid is mainly the fluid coming from the Laowan granite magma, rather than metamorphic fluid. Meanwhile, comparison studies on REE features between minerals from the deposit ores and related geological bodies in the deposit show that REE characteristics of minerals can serve as an indicator of ore-forming fluid properties and sources, while the REE characteristics of the bulk samples (such as deposit ores, granites and wall rocks) can not trace the source of the ore-forming materials exactly.
Keywords: LAOWAN GOLD DEPOSIT; ORE-FORMING FLUID; RARE EARTHS; REE GEOCHEMISTRY; SOURCE OF THE ORE-FORMING MATERIAL; COMPOSITION; GOLD DEPOSITS; MEASUREMENTS; ORES; PYRITES; QUARTZ; RARE EARTH ELEMENTS; DEPOSIT ORES; HENAN PROVINCE; INDUCTIVELY COUPLED PLASMA-MASS SPECTROMETRY (ICP-MS); ORE FORMING FLUID; GEOCHEMISTRY